Utilization of critical stroke rate in interval training of competitive swimmers - Funai, Y.; Matsunami, M.; Taba, S. (Japanese Journal of Sciences in Swimming and Water Exercise, 2016)
The purpose of this study was to determine whether Critical Stroke Rate (CSR) is effective as an index of intensity endurance interval training in competitive swimmers. CSR was expressed as the slope of the regression line between the number of stroke cycles and time. Seven collegiate competitive swimmers performed maximal 200 m and 400 m front crawl trials for CSR and Critical Swimming Velocity (CV). Subsequently, swimmers were instructed to perform a 4 × 400 m swimming test at CSR using a tempo trainer (interval test). Mean swimming velocity during the interval test was correlated significantly with CV (r=0.880, p<0.05). In the interval test, stroke length, blood lactate and RPE were also significantly increased (2.51±0.10 to 2.55±0.11m/stroke, 3.1±0.4 to 4.8±0.7mmol/L, 13.6±0.3 to 16.7±0.7, respectively) with the increase in swimming velocity. CSR is considered to be effective as an index for endurance interval training. Moreover, it is also suggested to be able to monitor stroke length in endurance interval training at CSR.